200 Monas : a novel - Saenz, Jan (Little, Brown and Company, 2026)
Arvy Keening is tantalizingly close to leaving her college years at Westheimer University behind her and starting her new Big Pharma internship. The problem? Arvy just found 200 hits of Molly in her dead mother's closet. When two drug dealers come to collect what they are owned, they revel that the pills are not Molly, but Mona -- a rare pharmaceutical that induces intense orgasms. The dealers give Arvy an ultimatum: Sell 200 Monas in 48 hours or die. Arvy recruits Wolf, Westheimer's resident drug dealer who happens to be infuriatingly charming and distractingly sexy. In a race against the clock Arvy and Wolf barrel through their college town, leaving a series of erotic shenanigans in their wake; appealing to horny co-eds, lonely barflies, and a mysterious sorority. --